Mitigating Misinformation Toolkit: A Medical Student Role-Play Curriculum on Communication Techniques to Facilitate Vaccine Misinformation Conversations - Cristina Pelin; Maya Vasser; Marie Cavuoto Petrizzo; Michael Cassara; Renee McLeod-Sordjan; Joseph Weiner; Samara Ginzburg (Association of American Medical Colleges, 2024)
Introduction The COVID pandemic and affiliated infodemic led to widespread health misinformation, generating confusion and distrust. Physicians must identify and address misinformation, with attention to cultural/health literacy, equity, and autonomy. Most medical students receive training in core communication techniques but are rarely taught how to combat misinformation with patients and lack opportunities for practice in diverse settings. Methods We used mixed methods to evaluate the impact of a role-play-based training curriculum on 44 third- and fourth-year medical students' comfort and confidence applying ask-respond-tell-seek solutions (ARTS) and motivational interviewing (MI) to discuss vaccine hesitancy, using COVID-19 as an example. There were three training iterations: prior to volunteering at a community health fair, during a medicine clinical rotation, and during a pediatrics rotation. Pre- and postsession questionnaires were administered. Likert-scale questions assessed comfort and confidence using ARTS and MI. Narrative responses focused on previous experiences with vaccine hesitancy, challenges faced, and session takeaways. Results Students' comfort, confidence with ARTS/MI, and self-reported ability to discuss COVID-19 vaccinations improved as measured by pre- and postsession surveys (p < .05). Qualitatively, students reported increased confidence delivering recommendations in plain language and exploring patients' thought processes behind choices. Discussion Reinforcement of core communications strategies in medical school can positively impact trainees' ability and ease addressing misinformation. We recommend this 45-minute training session to effectively increase medical students' comfort and confidence in discussing COVID-19 vaccines with patients. It can be adapted to any health professions school with an existing communications thread.